Clinical evaluation of qingre jiedu quyu decoction in the treatment of systemic lupus erythematosus and its effect on NLRP3 inflammatory bodies - YaXuan Fan; Caijin Cao; Zhiying Wu; Weidong Xu (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2020)
Objectives: To evaluate the clinical efficacy of Qingre Jiedu Quyu Decoction in the treatment of Systemic Lupus Erythematosus (SLE) and its effect on NLRP3 inflammatory bodies.  Methods: From January 2017 to December 2019, 74 patients with SLE were randomly divided into control group and observation group. The patients in the control group were given routine treatment(prednisone combined with immunosuppressive (hydroxychloroquine)). The patients in the observation group were treated with Qingre Jiedu Quyu Decoction on the basis of routine western medicine. The differences of related indexes and the changes of NLRP3 inflammatory bodies between the two groups before and after treatment were compared.  Results: The total effective rate was 94.59% in the observation group and 75.67% in the control group, there was significant difference between the two groups (P < 0.05). After treatment, the SLEDAI score, NLRP3,IL-1 β and IL-18 in peripheral blood of the two groups were significantly improved compared with those before treatment(P < 0.05), and the observation group was superior to the control group (P < 0.05). There was no significant difference in adverse reactions between the two groups (P > 0.05). Conclusions: Qingre Jiedu Quyu Decoction had certain clinical effect in the treatment of SLE. After treatment, the index of NLRP3,IL-1 β and IL-18 in peripheral blood of the observation group decreased more obviously than that of the control group (P < 0.05). Fund project: Funded by the National Natural Science Foundation of China in 2018-2018-40-0561; Young backbone talents training project of Traditional Chinese medicine in Jiangxi Province ;The molecular mechanism of nanorealgar in the treatment of SLE was explored from the B cell autophagy pathway which mediated by cAMP-Rap2B-PLCε-IP3R/Ca2+.